Mitochondrial dysfunction as a therapeutic nexus in HFpEF: therapeutic target and pharmacological advances - Yue, Tian; Zheng, Dezhi; He, Jian; Xiong, Shiqiang; Xu, Junbo; Hou, Jun (Frontiers in Pharmacology, 2025)
Heart failure (HF) with preserved ejection fraction (HFpEF) accounts for approximately 50% of all HF cases, and its incidence continues to rise with population aging and the surge in metabolic diseases. Unlike heart failure with reduced ejection fraction (HFrEF), HFpEF lacks effective therapeutic regimens to improve prognosis, with a 5-year mortality rate as high as 50%. Mitochondrial dysfunction, as a key link connecting metabolic disorders and abnormal myocardial systolic and diastolic function, has become a critical mechanism in the pathophysiology of HFpEF and a potential therapeutic target. This review systematically elaborates on the molecular mechanisms in HFpEF, such as mitochondrial energy metabolism disorders, dynamic imbalance, oxidative stress injury, and calcium signal dysregulation, comprehensively reviews the evidence for the effects of marketed drugs and drugs in clinical trials that improve mitochondrial function, and simultaneously explores emerging therapeutic strategies targeting mitochondria. This review aims to provide a theoretical reference for mechanistic research and drug development of HFpEF and promote the application of precision therapy targeting mitochondrial dysfunction in clinical practice.